Fixation of the Ajust minisling based upon cadaveric study - Hubka, Petr; Nanka, Ondrej; Martan, Alois; Svabik, Kamil; El-Haddad, Rachid; Masata, Jaromir (International urogynecology journal, 2013)
INTRODUCTION AND HYPOTHESIS: The objective was to describe the fixation site of the anchor of the Ajust mid-urethral minisling. METHODS: This cadaveric study was based on a group of 11 formalin-embalmed bodies with legs positioned in 30° flexion and 30° abduction, and a group of five fresh-frozen bodies with legs positioned as normal during the procedure. The groups were later compared. The fixation site was dissected and described. The distance to the obturator bundle was considered as the primary safety parameter. To compare the groups of fresh-frozen bodies and formalin-embalmed bodies, the Student's t test and Mann-Whitney test were used. RESULTS: In the group of formalin-embalmed bodies the mean distance from the anchoring device to the obturator nerve was 4.23 cm. In 19 cases out of 22 the anchor was within the complex of the obturator membrane and obturator muscles. In the group of fresh frozen bodies the mean distance to the obturator nerve was 3.15 cm. In 9 cases out of 10 the anchor was in the complex of the obturator membrane and obturator muscles. CONCLUSION: The distance from the anchor to the obturator nerve was more than 2 cm in all cases. Correct placement in the obturator membrane was achieved in 65.6 % of cases. In 87.5 % of cases the anchor was placed within the complex of obturator membrane and obturator muscles.
Keywords: Patient Positioning; mrtvola; polohování pacienta; Suburethral Slings; implantace protézy; Cadaver; suburetrální pásky; pánev; disekce; kryoprezervace; Cryopreservation; Prosthesis Implantation; ženské pohlaví; Humans; Prosthesis Retention; Embalming; Obturator Nerve; balzamování; nervus obturatorius; retence protézy; Pelvis; Dissection; Female; lidé